Tear function and abnormalities of ocular surface: relationship with subjective symptoms of dry eye in lbadan, Nigeria (2008)
Objective: To determine the relationship between tear function and ocular surface abnormalities with subjective symptoms of dry eye. Methods: Patients with various ocular irritation symptoms suggestive of dry eye were examined for tear break up time (TBUT), Schirmer's test 1, and Rose Bengal staining pattern. They were compared with a group of asymptomatic healthy subjects. Results: There were 63 subjects, mean age 43.8 years (+/-14.7 years) with various complaints of dryness presenting as having irritation or foreign body sensation. A group of 17 asymptomatic subjects, mean age 42.1 years (+/-12.7 years) were studied as controls. There were 22 (34:.9 %) males and 41(65.1%) females in the symptomatic group while the control group had 4 (23.5%) males and 13(76.5%) females. Ocular irritations included itching 38(60.3%), pricking and itching 10 (15.9%). Mean Shirmer's test value were lower for symptomatic, subjects (mean 14.5mm +/-12.3 right eye; 14.9mm+/-12.4 left eye), compared to the controls (23.0mm +/-13.4 right eye; 17. 9mm +/-13.4 Ieft eye) P=0.02, for right eye and 0.4 for left. The mean TBUTwere also lower amongst the symptomatic subjects (10.5 seconds, right eye and 10.1 seconds left eye), while for controls mean TBUT was 12.7.,seconds right eye and 12.1 seconds left eye (P=0.2). Fifty -six out of 126 (46.8%) eyes of all symptomatic subjects compared to 7 out of 34 (20.6%) eyes of asymptomatic subjects had positive staining of conjunctiva with rose Bengal (p=0.06). For subjects with itching as the primary symptom 44.7% of them as opposed to 23.5% of the controls were likely to stain positive with rose Bengal, (sensitivity of itching as screening tool for dry eye was 81%, specificity 38.2%). Itching and pricking sensation together (sensitivity 46.2% and specificity improved to 65%). Rose Bengal grades were also inversely correlated with mean Schirmers values (Pearson correlation -0.429; P = 0.001) and TBUT (Pearson correlation -0.316, P=0.005). Conclusion: Itching and other ocular irritation symptoms may be indicative of underlying abnormal tear function and ocular surface damage, their presence calls for further examination for tear deficiency and prompt institution of treatment for dry eye